2002
DOI: 10.1302/0301-620x.84b7.0841009
|View full text |Cite
|
Sign up to set email alerts
|

Hemicortical allograft reconstruction after resection of low-grade malignant bone tumours

Abstract: Low-grade surface tumours of bone may theoretically be treated by hemicortical resection, retaining part of the circumference of the cortex. An inlay allograft may be used to reconstruct the defect. Since 1988 we have performed 22 hemicortical procedures in selected patients with low-grade parosteal osteosarcoma (6), peripheral chondrosarcoma (6) and adamantinoma (10). Restricted medullary involvement was not a contraindication for this procedure. There was no evidence of local recurrence or distant metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…With the navigation guidance, we could reproduce the planned resection without any help of landmark measurements or intraoperative fluoroscopy. Some authors have reported the use of multiplanar osteotomies or hemicortical resection to treat select patients with bone sarcoma [1,3,5]. Our results in Patients 1, 5, 6, and 8 also suggest multiplanar osteotomies or hemicortical resection are possible around bone tumors.…”
Section: Discussionsupporting
confidence: 63%
“…With the navigation guidance, we could reproduce the planned resection without any help of landmark measurements or intraoperative fluoroscopy. Some authors have reported the use of multiplanar osteotomies or hemicortical resection to treat select patients with bone sarcoma [1,3,5]. Our results in Patients 1, 5, 6, and 8 also suggest multiplanar osteotomies or hemicortical resection are possible around bone tumors.…”
Section: Discussionsupporting
confidence: 63%
“…Given the high risk of local recurrence with a contaminated margin [2] and the resulting poor prognosis, many physicians are reluctant to perform a resection that achieves less than generously wide margins [1,2]. In contrast, some authors have reported no local recurrences and no nonunions, with a resection technique used for low-grade surface osteosarcomas that retains part of the cortical circumference [1,8,19]. This technique, termed hemicortical or hemicylindrical resection, removes the tumor while maintaining a portion of the host cortex to enhance healing and function [1,8,19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some authors have reported no local recurrences and no nonunions, with a resection technique used for low-grade surface osteosarcomas that retains part of the cortical circumference [1,8,19]. This technique, termed hemicortical or hemicylindrical resection, removes the tumor while maintaining a portion of the host cortex to enhance healing and function [1,8,19]. In high-grade tumors near joints, one report suggests trying to save the articular surface by performing a transepiphyseal osteotomy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the advantages of the reversed shoulder prosthesis with our experience in limb-saving procedures for malignant bone tumors and metastases of the hip or knee prompted us to choose an allograft-reversed prosthesis reconstruction [7][8][9][10]14]. Because of the length of the prosthetic stem, we were able to bridge the allograft and achieve stable fixation in the distal part of the humerus.…”
Section: Discussionmentioning
confidence: 99%